ETIKA PERILAKU POLITIK ORGANISASI - M. Yusuf Azwar Anas (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2017)
The purpose of this paper is to explain the ethics in politics behavior, especially in the organizational environment, not in practical political organizations. Organizational politics is needed in order to win business competition. In achieving business objectives requires the involvement of leaders in making decisions, the various interests in the decision-making process many colored organizational politics. The application of organizational political skills is much influenced by the behavior of every worker, attitude choice options becomes the determinant factor in the success of the organization, especially employee satisfaction in do work activities. Some offers of political behavior are explained to be an option in applying political strategy skills in organizations especially behavior and politics written by ibn khaldun in contrast to the concept of political behavior by Niccolo Machiavelli, 1469-1527